Determination of Participation of Khorramabad Basin's Sub-Basins in Peak Discharge and Runoff Volume to Find the Prioritization in Flood Control - Samira Koshki; Ahmad Mazidi (جغرافیا و پایداری محیط)
One of the most proceedings in flood management projects is the study participation rate of different sub-basins a drainage basin in determination of various component of the output flood of basin. Considering the lack of hydrometric stations in all sub-basin outlet, performance of these target requires the simulation of rainfall–runoff in sub-basins by hydrological models. In this research, the HEC – HMS rainfall-runoff model was used in order to determining the amount of output flood in each sub-basin and its participation rate in output flood of Khorramabad drainage basin in Lorestan province. For this purpose, after gathering rainfall and flood data from synoptic and hydrometric stations which were located inside and outside of the basin and checking of the data, 5 shower occurrences and simultaneity runoff for calibration and validation of model were used. CN map was extracted in ArcGIS by using the state information of vegetation cover, soil and land use of drainage basin. Rainfall hyetograph was the input of the model in different return period including 2, 5, 10, 20, 50, 100 years and then with sequential deletion of sub-basins from the simulation was determined its influence rate in peak discharge and flood outflow volume from the basin. The results showed that the priority of participation in peak discharge and flood volume was dedicated to sub-basin 5 because it is larger than other. To access the flood features without the effect of area, the highest discharge peak was for the sub-basins 4 and the priority for flood volume was dedicated to the 2 sub-basins. The results have provided the correct management of flood by the management of critical sub-basins in case study area.